807 ASSOCIATION OF BOLUS TRANSIT TIME ON BARIUM ESOPHAGOGRAM WITH ESOPHAGEAL PERISTALSIS. (17th September 2021) - Razia, Deepika; Trahan, Amy; Giulini, Luca; Baboli, Komeil M; Mittal, Sumeet K
Abstract:  : The threshold criteria for diagnosing ineffective esophageal motility (IEM) has changed over the years and is based on the proportion of failed and weak peristalses. Bolus transit time (BTT) on barium esophagogram (BE) can intuitively be the 'gold standard' for assessing the effectiveness of esophageal peristalsis. The aim of this study was to associate upright and prone BTT with esophageal peristalsis and dysphagia in patients with normal lower esophageal sphincter (LES) parameters. Methods: Patients with normal LES on high-resolution manometry (HRM) who also had a standard-protocol BE from 2017 to 2020 were included. Patients with previous foregut surgery, hiatal hernia, jackhammer esophagus, distal esophageal spasm, fragmented peristalsis, and those with < or > 10 single swallows on HRM were excluded. Based on the number of normal swallows (DCI >450 mmHg.s.cm ), the patients were divided into 11 groups (10 normal to 0 normal). Upright and prone BTT were measured on BE. Fractional polynomial and logistic regression analysis were used to study association (along with rate of change) between BTT, dysphagia, and peristalsis. Results: In total, 146 patients met the inclusion criteria. Prone BTT increased in tandem with a decrease in the number of normal peristalses (p < 0.001), but no difference was noted in upright BTT (p = 0.317). Two deflection points were noted on the association between peristalsis and prone BTT at 50%, 40 seconds and 30%, 80 seconds on the y and x-axes, respectively, after which declining peristaltic function was independent of prone BTT. Patients with prone BTT >40 seconds had nearly 6-fold higher odds of having zero normal peristalses (p = 0.002). Increasing prone BTT was associated with increasing dysphagia (p < 0.05). Conclusion: Prone, but not upright BTT, correlates with the proportion of normal esophageal peristalses and dysphagia. The phenotype of abnormal swallows (failed, weak) appears to have minimal impact on BTT. The current perspective of manometric classification may need to be adjusted to use the proportion of normal peristalses as a criterion.